Հայ ժողովրդական մեղեդիների նոտագրման առանցքային խնդիրների շուրջ - Աթանասյան, Նունե
Հայ երաժշտական ֆոլկլորագիտության կարևորագույն խնդիրներից մեկի՝ բանահավաքչական նյութի նոտագրման հարցերին նվիրված հոդվածը ներկայացնում է այս խնդրի լուծման ժամանակակից միջոցները, տեսակները։ Երկդարյա ժամանակաշրջանի ընթացքում անցնելով զարգացման տարատեսակ փուլեր ժամանակակից նոտագրման գործընթացը բավականին հղկվել է և զարգացել։ Սակայն, այնուամենայնիվ, այսօր հրատարակման պատրաստելով տարբեր ժամանակահատվածներում նոտագրված նյութը, հասկանալի է դառնում, որ նույնականացման անհրաժեշտություն կա. տարբեր նոտագրողների կատարած անուրանալի և բարձր մասնագիտական մակարդակով կատարած աշխատանքները մեկ ժողովածուում ընդգրկելու համար դրանք նորովի համակարգման և վերանայման կարիք ունեն։ The article, devoted to one of the most important prob- lems of Armenian musical folkloristics - the notation of folklore material, presents modern means and types of solution to this problem. During a two-century period, the modern process of notation has improved and developed, passing through various stages of development. However, today, preparing the material recorded in different chronological periods for publication, it is clear that there is a need to identify this process. Undoubtedly, the highly professional work done by different transcribers needs to be coordinated and revised in order to compile today a single collection of transcription principles. Methods and materials: Preparing the material recorded in different eras for publication today, the main collections containing samples of Armenian musical folklore were studied using the comparative method. Analysis: The basis of the comparative analysis was the registration of the scale and the notes of the melody of the song, and the fixation of its pitch. The complexity of the problem is that one of the responsible works performed by the editor of the collection of folk songs is to correct, regulate and homogenize the material. Results: Notational disagreements do not at all degrade the quality of presentation of the material and its perception, however, it becomes obvious that the clarification of notation issues will help to form a database of principles, a system, thanks to which it will be possible to further improve and regulate the quality of notation of folk songs. В статье, посвященной одной из важнейших проблем армянской музыкальной фольклористики - нотации фольклорного материала, представлены современные средства и виды решения этой проблемы. В течение двухвекового периода современный про цесс записи совершенствовался и развивался, проходя различные этапы развития. Однако сегодня, готовя к публикации материал, зафиксированный в разных хронологических периодах, становится ясно, что есть необходимость в идентификации данного процесса. Методы и материалы: Сегодня, при подготовке к публикации материала, записанного в разные эпохи, с помощью сравнительного метода, были изучены основные сборники, содержащие образцы армянского музыкального фольклора. Анализ: Основой сравнительного анализа послужила запись звукоряда и нот мелодии песни, фиксация ее высоты. Сложность проблемы в том, что одной из ответственных работ, выполняемых редактором сборника народных песен, является корректировка, регламентация и гомогенизация материала. Результаты: Нотационные разногласия ничуть не ухудшают качество изложения материала и его восприятия, однако становится очевидным, что выяснение вопросов нотной записи поможет сформировать базу принципов, систему, благодаря которой можно будет в дальнейшем улучшать и регулировать качество нотной записи народных песен.
Keywords: Հայկական երաժշտություն